Between Bavaria and East Prussia. Geographical, historical and cultural connections and contemporary perception of the heritage of the Prussian lands - Lewandowska, Izabela (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
Today’s Bavaria, the richest land in modern Germany, consists of the historical lands of Franconia and Swabia. East Prussia no longer exists, but the memory of it is still alive among its former residents, who were displaced or left intentionally after World War II. In the chapter I will show similarities and differences in the geography and the historical and cultural relationships over the centuries. In the second part of the chapter I will focus on the heritage of the Prussian lands, as presented by the Center of East Prussia Culture in Ellingen, housed in the former palace of the German Order (a.k.a. the Teutonic Knights) in the central part of Bavaria. The studies conducted during my six-week-long scientific internship at Ellingen have enriched my personal observations and allowed me to write the chapter.